PERAN ETIKA PROFESI DALAM IMPLEMENTASI HAK ASASI MANUSIA - Jeni Dianiati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Profession is a term that refers to a job that requires special expertise or skills. Where in practice every person since birth has been specially equipped with talents by our creator and it is our responsibility to apply them properly and correctly for our survival and that of others. In general, the notion of professional ethics is an ethical attitude that is owned by a professional as an integral part of the attitude of life in developing their duties and applying general ethical norms in specific fields (professions) in human life.